From Poverty to Peace: The Role of Youth Entrepreneurship in the Zakat-Waqf-Based Economy - Nurul Hilmiyah; Gunawan Baharuddin; Aulia Keiko Hubansyah; Yuli Ardianto; Safitri Siswono; Ridwan Ismail; Cafrina Lisyani Sudzan; Mariyah Sujana; Maudyna Tasya Ardianti (Abdi Implementasi Pancasila:Jurnal Pengabdian kepada Masyarakat, 2026)
Poverty remains a structural problem faced by many developing countries, including Indonesia. This condition not only limits the fulfillment of basic needs but also contributes to social inequality, low human resource quality, and potential social conflict. In the perspective of Islamic economics, zakat and waqf are strategic instruments for wealth redistribution and community economic empowerment. However, in practice, the utilization of these instruments is still largely consumptive and has not optimally created long-term economic independence. This international community service program aims to strengthen youth entrepreneurial capacity through a zakat–waqf-based economic approach. The program was implemented through online seminars, entrepreneurship training, focused group discussions, and mentoring for the development of zakat-waqf-based business models. The study applied a qualitative descriptive approach using a case study method to understand the dynamics of youth empowerment within Islamic social finance. The results show that the program successfully increased participants’ understanding of Islamic economic instruments, strengthened social entrepreneurship mindsets among youth, and encouraged the development of business ideas that integrate social impact and sustainability. The program also contributed to strengthening social solidarity and promoting inclusive economic empowerment. Therefore, integrating youth entrepreneurship with productive zakat and waqf management can serve as an alternative strategy for poverty alleviation and sustainable economic development.